Participation budgeting in Poland. Analysis of legal regulations - Urbański, Daniel (The Copernicus Journal of Political Studies, 2019)
The realization of citizens’ (participatory) budgets has become one of the fixed duties of the authorities of Polish towns and cities. Local governments are to willingly engage citizens and enable them to make decisions related, among other things, to local finances. Social consultation is an exceptionally important process allowing the administration to get acquainted with public opinion or proposals put forward by the citizens who are – directly or indirectly – affected by the issue in question. Until 2019, Polish participatory budgets were based on the provisions of the Gmina Self-Government Act of 8 March 1990; or, more precisely, based on Article 5a, which provided that when it comes to issues which are important for a gmina, social consultations with citizens may be conducted. However, social consultations are not binding. On the other hand, for participatory budgets, a different solution has been adopted. Gmina authorities declared that the decisions made by citizens will be recognized as binding (Kraszewski & Mojkowski, 2014). The amendment of the provisions of the relevant acts (already operative) urges the author of the present paper to pose a question about the necessity of legal regulations to the mechanism of a participatory budget. Do Polish budgets actually call for such provisions? And, will particular solutions included in the Act lead in the near future to a diminishment of the budget’s role in shaping participation among citizens? Taking heed of the imperfections of these provisions, the present paper constitutes an attempt to discover the problems posed by the Act that local governments are facing. The main research method is an analysis of sources; and in particular, an analysis of the provisions of the Act of 11 January 2018 on amending certain others to increase the participation of citizens in the process of electing, operating and controlling certain public bodies (Dziennik Ustaw, 2018, item 130).